The influence of humoral factors of homeostatistic proliferation on t-regulatory cells in vitro - D. V. Shevyrev; E. A. Blinova; V. A. Kozlov (Бюллетень сибирской медицины)
Aim. The aim of this study was the investigation of the influence of humoral factors of homeostatic proliferation IL-7 and IL-15 on T-regulatory cells in healthy donors.Materials and methods. The study included 15 conditionally healthy donors. Phenotyping and evaluation of expression changes of transcription factor FoxP3 and the main functional molecules on T-regulatory cells such as PD-L1, CTLA-4 and HLA-DR during cultivation under IL-7, IL-15 and anti-CD3 stimulation combined with IL-2 were performed by flow cytometry. Also, we estimated proliferation intensity of T-regulatory cells in the course of cultivation.Results. We revealed that humoral factors of homeostatic proliferation can effectively support a pool of T-regulatory cells during cultivation by number and phenotype and can maintain expression of important molecules such as PD-L1 and HLA-DR on regulatory T-cell surface. In addition, our study showed that IL-7 and IL-15 can cause relatively low T-regulatory cells proliferation in comparison to CD4+- lymphocytes.Conclusion. The observed ability of homeostatic proliferation factors to maintain T-regulatory cells pool presumably can play an important role in lymphopenic conditions when the number of effector cells is decreased and the insufficiency of interleukin IL-2 is observed, which plays a primary role in the homeostasis of T-regulatory cells in normal conditions.